Essential Happiness for Human Beings in Perspective of Ibn Sina - Rasid, Rasid; Sabirin, Falah (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
There are some factors which can influence the characters and mindset of human beings. One of the factors is world view or the principle owned in life, therefore, that principle also influences the human’s life in the world. Human beings as the being that have free will, all of voluntary actions are effect from the knowledge and willingness. Furthermore, both good and bad deeds are sourced from knowledge and willingness. We can analyze the phenomena of human’s actions by seeing the knowledge they have. Some human beings have believed that happiness is based on material things. This viewpoint encourages them to achieve happiness with various ways they use. In this sense, the viewpoint of happiness causes human actions such as consumerism, terrorism, corruption, and abusing of drugs, meanwhile those actions do not match and correspond to the rationality of human beings as the differentia from the other species. By this foundation, the concept of happiness should be re-conceptualized, which is happiness that coordinates to the rationality of human beings. In this case, the worldview regarding the essence of human beings and the goal of creation determines the actions that will be done. Ibn Sina, who represents the philosophy of peripatetic in his works, has described and established the arguments regarding the essential happiness for species of human beings. Happiness will be achieved, if human beings can actualize the final goal of the creation (al-khalq). The final goal of one species can be seen from the differentia of the species. Therefore, the essential happiness for human being is the actualization of the rationality; theoretical and practical reason.This thesis aims to describe the viewpoint of Ibn Sina deeply regarding the essential happiness for human being and how to achieve that happiness through the realization of final goal of human being as the rational animal which becomes differentiate from other species. Ibn Sina is consistent with his foundation of philosophy through the demonstration method of establishing the existence of something.